The relationship between body composition and diatary habits in the university faculty members - Fatma Arslan; Ozden Tasgın; Sefika Dilek Guven; Aysegul Ozcan; Ozen Ozbay Ozbas (Türk Spor ve Egzersiz Dergisi)
The aim of this study was to determine the relationship between eating habits and body composition of the university personnels. The sampling of this research consisted of academic and administrative personnels from the university (68 female and 124 male personnels). Body weight and composition were measured with a Tanita instrument. Data were collected by performing a questionnaire including 33 items. For the statistical analysis, frequency and percentage (%) distributions, Chi-Square test and Pearson correlations were used. For females, 38.9% of the university members, 30% of the instructors and 32.5% of the administrative personnels and for men, 31.6% of the university members, 38.5% of the instructors and 27.2% of the administrative personnels had two meals in a day. Both female and male administrative personnels had more junk food consumption than the others. In this study, there was more fat milk/yogurt consumption that was correlated with body composition parameters in the female university members (p lt;0.05). This study showed that the participants generally had unhealthy lifestyles and the critical values in waist circumferences and hip circumferences, waist-height ratio, and waist-hip ratio from body composition parameters. Because of this, healthy lifestyles-associated behaviors (exercises, physical activities, dietary habits and responsibilities of health, e.g.) must be developed among the university faculty members and other employees.